Legal Protection for Consumers Against Online Sales of Frozen Food That Do Not Have A Distribution Permit from The Food & Drug Supervisory Agency - Manurung, Rosa Desi Natalisma; Sidauruk, Jinner; Gultom, Meli Hertati (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
With so many frozen foods sold online, they must meet various requirements and procedures before they can be marketed and disseminated to the public, one of which is by including a distribution permit number. The provisions of a distribution permit are intended to protect the public from unsafe, low-quality and non-nutritious food products. However, some consumers still do not pay attention to the distribution permit. The problem that arises in this research is how legal efforts are made by consumers for processed frozen food that does not have a distribution permit that is traded online in terms of Legal Protection for Consumers in the Distribution of Unlicensed Frozen Food by BPOM in terms of Law Number 8 of 1999 concerning Consumer Protection, Law Number 18 of 2012 concerning Food, Food and Drug Monitoring Agency Regulation Number 8 of 2020 concerning the Supervision of Drugs and Food Circulated Online, Law Number 36 of 2009 concerning Health and how the responsibility of the Center for Food and Drug Control (BBPOM) for the circulation of frozen food products that do not have a distribution permit. To answer the problem, it is handled through the application of a normative legal research approach, which is a method that refers to legal norms carried out by literature study. The results of this study show that consumers are protected under several laws. Basically, consumers know about the importance of the distribution permit for cold processed food products, but they do not fully understand consumer protection. And shows that the Food and Drug Supervisory Agency Regulation Number 8 of 2020 concerning the Supervision of Drugs and Foods circulated online requires processed food products sold online to have a distribution permit and ensure the safety and quality of processed food products. To supervise the circulation of processed food, BPOM builds and assists businesses and cooperates with the Health Office. And the attitude of responsibility of business actors is in accordance with Article 19 of the UUPK.